Until I get off parole … then I can swim in it if I want to: Facilitators of and barriers to drug use among formerly incarcerated Black drug offenders. Issue 1 (2nd January 2019) - Mkuu, Rahma; Rowell-Cunsolo, Tawandra L.; Harvey, Idethia Shevon
ABSTRACT: Black Americans are overrepresented among those incarcerated for drug-related offenses. Drug use, postincarceration, is associated with high risk of recidivism and overdose deaths. We explored factors influencing drug use among former Black drug offenders. Qualitative interviews with 30 Black Americans released from prison within the past year explored drug behavior as well as institutional, environmental, and social factors that influence drug use. Findings show participants reentered drug-enticing environments and social networks. Being on parole, drug programs, and social support influenced abating drug use. Drug interventions postincarceration should consider the environment and social networks as leverage points for behavior change.